THE THEORY OF BIOLOGICAL JUSTICE IN LEGAL PHILOSOPHY AND ITS APPLICATION IN JUDGES’ DECISIONS - Amran Suadi (Pusat Strategi Kebijakan Hukum dan Peradilan Mahkamah Agung RI, 2020)
Justice is one of the legal goals that judges want to uphold. Since justice is subjective and individual, it cannot be separated from the place, time, and others, which greatly affects the judges' sense of justice. Justice is becoming more important when the 'question of law' is about to be applied to the 'question of fact.' Justice is defined as a value to create an ideal relationship among humans. They are entitled according to law and morality as stated by the popular doctrine